Pemahaman Masyarakat Muslim terhadap Jaminan Produk Halal dalam Penyembelihan Hewan (Studi atas QS. Al-Baqarah: 168 dan QS. Al-Maidah: 3 di Kelurahan Pasar Baru) - Adrianto; Haslinda (Jurnal Ilmiah Al-Furqan: Al-qur’an Bahasa dan Seni, 2025)
This study examines the understanding of the Muslim community in Pasar Baru Village regarding halal product assurance in animal slaughtering based on QS. Al-Baqarah (2): 168 and QS. Al-Ma’idah (5): 3. Employing a qualitative approach through library research, this study analyzes Qur’anic exegesis, Islamic jurisprudence on slaughtering, and Indonesian halal certification regulations. The findings reveal that the community’s understanding extends beyond technical slaughtering procedures to encompass a normative religious awareness that integrates Qur’anic values, classical exegetical interpretations, and contemporary halal assurance systems. The theoretical contribution of this study lies in strengthening the conceptual linkage between Qur’anic exegesis, fiqh al-dhabh, and the modern Halal Product Assurance System (SJPH), which are often examined separately. The novelty of this research is found in its conceptualization of community understanding as a form of collective religious consciousness that mediates between sacred texts and state regulation, particularly Law No. 33 of 2014 on halal Product Assurance. This study demonstrates that halal assurance is not merely a legal-technical framework, but a manifestation of lived Islamic ethics rooted in Qur’anic teachings.